(untitled) (Revista de História da UEG (REVHIST), 2024)
This article proposes an analysis of the world of work of railway workers in Ceará, focusing on subjects residing in the city of Reriutaba, specifically in the permanent category, responsible for the maintenance and conservation of the railway line. In this sense, we sought to highlight the narratives and memories of the workers, aiming to understand the identity project that these individuals aimed to develop. In this work, silence and forgetfulness were considered as elements of analysis of their narratives when mentioning penalties. Therefore, the main methodology was Oral History, dialogued with the crossing of written documents, one of them being the railway workers work sheets that contain the trajectory from entry to exit from the service. Therefore, it was demonstrated that, in addition to the nostalgia of having been a railway worker, there were conflicts in everyday life. Keywords: Memories. Railway workers. Identity. Punishments.